2009
DOI: 10.1097/sla.0b013e3181bdd5a8
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications After Transthoracic Esophagectomy for Cancer of the Esophagus and Gastroesophageal Junction Are Correlated With Early Cancer Recurrence

Abstract: This study indicates a correlation between complications and early recurrence and its timing. Modified Clavien classification, beside R1-status and EC LNI, appears to be a useful prognostic indicator of early recurrence and its timing. Achieving esophagectomy without postoperative complications is of utmost importance also for oncologic reasons given its negative potential on early oncologic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
161
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(188 citation statements)
references
References 15 publications
14
161
2
2
Order By: Relevance
“…However, several other studies have concluded that surgical complications have no negative effect on survival rates and that these rates depend exclusively on the pathological stage of the tumor 12. Lerut et al 13. have reported that the modified Clavien classification, in addition to the microscopic residual tumor and extracapsular lymph node involvement, is a useful prognostic indicator of early recurrence and its timing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several other studies have concluded that surgical complications have no negative effect on survival rates and that these rates depend exclusively on the pathological stage of the tumor 12. Lerut et al 13. have reported that the modified Clavien classification, in addition to the microscopic residual tumor and extracapsular lymph node involvement, is a useful prognostic indicator of early recurrence and its timing.…”
Section: Introductionmentioning
confidence: 99%
“…have reported that the modified Clavien classification, in addition to the microscopic residual tumor and extracapsular lymph node involvement, is a useful prognostic indicator of early recurrence and its timing. They have noted that achieving esophagectomy without postoperative complications is of utmost importance because of their potential negative effect on early oncological outcomes 13. Recent advances in endoscopic diagnosis and clinical radiology in Japan allow early detection of gastric cancer, and therapeutic strategies have been established in some clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of extracapsular nodal invasion is an independent prognostic factor [68,74,75,[78][79][80] and can be used to stratify patients according to the number of lymph nodes in which it is present. For example, in patients with extracapsular lymph node infiltration in only one lymph node, the median survival is M A N U S C R I P T…”
Section: Prognostic Implications Of Extracapsular Diseasementioning
confidence: 99%
“…Many previous studies [1][2][3][4][5][6][7][8][9] have demonstrated that the development of postoperative complications increased the risk of disease recurrence in various types of malignancies. Among surgical morbidities, infectious complications are the most frequent and directly related to surgery.…”
Section: Introductionmentioning
confidence: 99%